A new species of Characidium (Characiformes: Crenuchidae) from the rio Parnaíba basin, northeastern Brazil - Zanata, Angela M.; Ramos, Telton P. A.; Oliveira-Silva, Leonardo (Zootaxa, 2018)
Characidium tapuia, a new species apparently endemic to the rio Parnaíba basin, Brazil, is described. The new species is easily distinguished from congeners, except C. lanei, C. nana, and C. samurai, by having a broad and conspicuous dark lateral stripe, extending from the tip of snout to the end of caudal peduncle and by the absence of dark vertical bars on body of specimens larger than 23.0 mm SL. Characidium tapuia differs from the aforementioned species by a series of features, including 12 circumpeduncular scales (vs. 13 or 14 in C. lanei and C. samurai), presence of parietal branch of the supraorbital canal (vs. absence in C. lanei and C. nana), complete lateral line and adipose fin present (vs. lateral line incomplete and adipose fin absent in C. nana), and midlateral stripe with irregular borders (vs. lateral stripe with overall straight borders in C. samurai).